ERP & data warehousing in organizations issues and challenges - Grant, Gerald G. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2003)
The successful implementation and deployment of enterprise resource planning hinges on an organization's understanding of the complex and challenging issues involved in the process. And, the further development of information and communication technologies are presenting more challenges to organizations. This title attempts to provide the most recent research and findings concerning these issues, in order to provide practical assessments and suggestions for managers in the process of developing such systems